Microsatellite mapping of the gene causing weaver disease in cattle will allow the study of an associated quantitative trait locus. - Georges, M (1993)
A genetic disease in cattle, progressive degenerative myeloencephalopathy (weaver disease), is associated with increased milk production. This association could result from population stratification, from a pleiotropic effect of a single gene, or from linkage disequilibrium between the gene causing weaver disease and a quantitative trait locus (QTL) for milk production. To test these hypotheses, we performed an extensive linkage study in a bovine pedigree segregating for the weaver condition and identified a microsatellite locus (TGLA116) closely linked to the weaver gene (zmax, 8.15; theta, 0.03). TGLA116 and, by extension, the weaver locus were assigned to bovine synteny group 13. This microsatellite can be used to identify weaver carriers, to select against this genetic defect, and to study the effect of the corresponding chromosomal region on milk production in Brown Swiss and other breeds of cattle.